2022
DOI: 10.3390/jcm11030765
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Tuberculosis and Risk of Lung Cancer: A Systematic Review and Meta-Analysis

Abstract: Pulmonary tuberculosis (TB) is a known risk factor for lung cancer. However, a detailed analysis of lung cancer type, age, sex, smoking, and TB burden associated with geographic and socioeconomic status has not been performed previously. We systematically appraised relevant observational studies reporting an association between pulmonary TB and lung cancer. All studies were included in the primary analysis, and studies that used robust TB diagnostic methods, such as validated medical diagnostic codes, were inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 63 publications
0
29
0
Order By: Relevance
“…More recent systematic reviews found similar results in pulmonary [11,40] and non-pulmonary cancers [12] post-TB. In these studies, pooled risk of lung cancer ranged from 1.96 to 2.17 [11,12,40]. However, these systematic reviews all included studies with self-report data, which carry a critically high risk of recall bias.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…More recent systematic reviews found similar results in pulmonary [11,40] and non-pulmonary cancers [12] post-TB. In these studies, pooled risk of lung cancer ranged from 1.96 to 2.17 [11,12,40]. However, these systematic reviews all included studies with self-report data, which carry a critically high risk of recall bias.…”
Section: Discussionmentioning
confidence: 53%
“…They also found that the risk of lung cancer was over 10 times greater in the first 5 years following TB diagnosis, remaining elevated for more than 20 years after TB [39]. More recent systematic reviews found similar results in pulmonary [11,40] and non-pulmonary cancers [12] post-TB. In these studies, pooled risk of lung cancer ranged from 1.96 to 2.17 [11,12,40].…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…There is evidence in a literature using Meta-analysis indicated that Tuberculosis diagnosed at a young age is a risk factor for lung cancer, regardless of smoking history or other underlying disorders. This trend was more obvious among patients from high TB burden countries [ 12 ].…”
Section: Age Pulmonary Tuberculosis and Lung Cancermentioning
confidence: 99%
“…This has also become another important reason for the susceptibility of lung cancer in pulmonary tuberculosis patients with a history of smoking. Severe lung tissue damage mediated by the TB susceptibility locus sst1 is more significant in the occurrence of lung cancer caused by chronic TB infection [ 12 ]. Camilo Molina-Romero stated that Mycobacterium tuberculosis DNA can integrate into bronchial epithelial cells and induce lung neoplastic transformation [ 95 ].…”
Section: Dna Damage Of Pulmonary Tuberculosis and Lung Cancermentioning
confidence: 99%